Simultaneous removal of organic matter and nitrogen compounds by an aerobic/anoxic membrane biofilm reactor - Hasar, Halil; Xia, Siqing; Ahn, Chang Hoon; Rittmann, Bruce E. (Pergamon-Elsevier Science Ltd, 2008)
The hydrogen-based membrane biofilm reactor (MBfR) has been well studied and applied for denitrification of nitrate-containing water and wastewater. Adding an oxygen-based MBfR allows total-nitrogen removal when the input nitrogen is ammonium. However, most wastewaters also contain a significant concentration or organic material, measured as chemical oxygen demand (COD). This study describes experiments to investigate the removal of organic and nitrogenous compounds in the combined Aerobic/Anoxic MBfR, in which an Aerobic MBfR (Aer MBfR) precedes an Anoxic MBfR (An MBfR). The experiments demonstrate that the Aer/An MBfR combination accomplished COD oxidation and nitrogen removal for a total oxygen demand flux (i.e., from COD and NH4 oxidations) in the range of 1.2-7.2 gO(2)/m(2)-d for 4.5 psi (0.3 atm) oxygen pressure to the Aer MBfR, but was overloaded and did not accomplish nitrification for the total oxygen demand load higher than 14 g O-2/m(2)-d. Total-nitrogen removal was controlled by nitrification in the Aer MBfR, because the An MBfR denitrified all NO provided to it by the Aer MBfR. The overload of total oxygen demand did not affect COD oxidation in the Aer MBfR, but caused a small increase of COD in the An MBfR due to net release of soluble microbial products (SMP). (C) 2008 Elsevier Ltd. All tights reserved.
Keywords: BOD oxidation; Total-nitrogen removal; Total oxygen demand; Total oxygen flux; Membrane biofilm reactor